Experimental Approaches in Migration Studies - McKenzie, David (2012)
The decision of whether or not to migrate has far-reaching consequences for the lives of individuals and their families. But the very nature of this choice makes identifying the impacts of migration difficult, since it is hard to measure a credible counterfactual of what the person and their household would have been doing had migration not occurred. Migration experiments provide a clear and credible way for identifying this counterfactual, and thereby allowing causal estimation of the impacts of migration. The authors provide an overview and critical review of the three strands of this approach: policy experiments, natural experiments, and researcher-led field experiments. The purpose is to introduce readers to the need for this approach, give examples of where it has been applied in practice, and draw out lessons for future work in this area.